The Role of LPPOM MPU Aceh in the Framework of Halal Certification in Poultry Products - Oka Dian Kurniawati; Teuku Ahmad Yani; Teuku Muttaqin Mansur (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
Halal Qanun No. 8 of 2016 requires business actors to carry out halal certification, but the fact in the field is that many poultry slaughtering business actors do not implement halal certification. Writing this journal aimed to find out why business actors have not implemented halal certification and the role of LPPOM MPU Aceh in the context of implementing halal certification on poultry products. The method used was juridical-empirical, such as looking at applicable laws and facts in the field, primary and secondary data obtained through interviews include primary, secondary and tertiary laws. The results showed that the cause of business actors who had not been certified halal in the poultry slaughtering product business was because they had not met the standards set by LPPOM MPU Aceh so that LPPOM MPU Aceh had not been able to issue halal certificates. Regarding the perpetrators who have not met halal standards, LPPOM MPU Aceh has given 6 months to fix all deficiencies in business products. In fact, business actors do not fix it. LPPOM MPU Aceh is not strict in giving sanctions to business actors who have registered for halal certification but do not improve according to the specified halal accuracy